Enhancing nursing education via academic-clinical partnership: An integrative review - Thokozani Bvumbwe (Elsevier, 2016)
A competent nursing workforce is important for an effective healthcare system. However, concerns on the poor quality of nursing care and poor competencies among nursing students, nurses, and midwives are increasing in Malawi. Anecdotal notes from stakeholders show shortfalls in nursing education. Furthermore, a large gap between theory and practice exists. This study described the role of academic-clinical partnership in strengthening nursing education. A search of ScienceDirect, PubMed, Medline, and PsychINFO on EBCSOhost and Google Scholar was conducted using the following key words: academic-clinical collaboration, academic-clinical partnership, academic practitioner gap, and college hospital partnership or/and nursing. Furthermore, peer reviewed reports on academic-clinical partnership in nursing were included in the search. Thirty-three records from 2002 to 2016 were reviewed. Six themes emerged from the review: mutual and shared goals, evidence-based practice, resource sharing and collaboration, capacity building, partnership elements, and challenges of academic clinical partnership. The review highlighted that academic-practice partnerships promote shared goal development for the healthcare system. The gap between theory and practice is reduced by the sharing of expertise and by increasing evidence-based practice. Academic clinical partnership improves competencies among students and the safety and health outcomes of patients. The study concluded that the nursing education implemented within an academic clinical partnership becomes relevant to the needs and demands of the healthcare system.